Physicochemical and material properties of starches from three cultivars of Dioscorea rotundata - Ahmadu, Umaru; Agbomeji, Olamide; Yahya, Mohammed; Odeku, Oluwatoyin A. (Agriculture and Natural Resources, 2018)
Dioscorea rotundata (white yam, guinea yam or African yam) is the most important species of yam in West Africa because of its economic value and uses. Starches from three cultivars of Dioscorea rotundata namely, Giwa, Lagos, and Sule, were characterized for their physicochemical and material properties. The starches were evaluated using elemental and proximate analyses, scanning electron microscopy, X-ray powder diffraction analysis and density measurements. The results showed that the starch granules from the three cultivars of D. rotundata were oval-oblong in shape with a size range of 3.19-3.59 µm. The X-ray diffraction pattern of the starches from the three cultivars was of the C-type with relative crystallinity of 21%. The results showed that starches from the three D. rotundata cultivars had similar proximate, physicochemical and material properties. The starches had similar functionality, probably due to the similarities in their botanical sources. Thus, starches from the three cultivars of D. rotundata could be interchangeable as excipients in pharmaceutical tablets.